2000
DOI: 10.1128/mcb.20.1.416-427.2000
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Insulin-Responsive GLUT4 Storage Vesicles Isolated from 3T3-L1 Adipocytes

Abstract: Insulin regulates glucose transport in muscle and adipose tissue by triggering the translocation of a facilitative glucose transporter, GLUT4, from an intracellular compartment to the cell surface. It has previously been suggested that GLUT4 is segregated between endosomes, the trans-Golgi network (TGN), and a postendosomal storage compartment. The aim of the present study was to isolate the GLUT4 storage compartment in order to determine the relationship of this compartment to other organelles, its components… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
94
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(109 citation statements)
references
References 61 publications
14
94
1
Order By: Relevance
“…The great advantage of the present technique is that it allows for the first time the purification of membranes that can be observed to be insulin-sensitive without the use of reagents that can contaminate the preparations such as immunoglobulin polypeptides. This contrasts with other methods where membranes enriched with GLUT4 are obtained but do not seem to be reduced in abundance when cells are treated with insulin (16,67). The GLUT4-containing membranes purified by the method described here thus appear to be particularly excellent for the application of microsequencing techniques to identify resident proteins.…”
Section: Fig 11 Effect Of Inhibition Of Dynein Activity By Cytoplascontrasting
confidence: 44%
See 2 more Smart Citations
“…The great advantage of the present technique is that it allows for the first time the purification of membranes that can be observed to be insulin-sensitive without the use of reagents that can contaminate the preparations such as immunoglobulin polypeptides. This contrasts with other methods where membranes enriched with GLUT4 are obtained but do not seem to be reduced in abundance when cells are treated with insulin (16,67). The GLUT4-containing membranes purified by the method described here thus appear to be particularly excellent for the application of microsequencing techniques to identify resident proteins.…”
Section: Fig 11 Effect Of Inhibition Of Dynein Activity By Cytoplascontrasting
confidence: 44%
“…4), and this receptor is thought to be present mostly in recycling endosomes that apparently show only modest sensitivity to insulin (12,16). However, this problem also applies to GLUT4-containing membrane preparations obtained by immunoadsorption with anti-GLUT4 antibodies because GLUT4 is also present in the recycling endosome compartment (12,(15)(16)(17). Furthermore, immunoelectron microscopy shows that virtually all of the membrane vesicles obtained by the method described here do actually contain GLUT4 (Fig.…”
Section: Fig 11 Effect Of Inhibition Of Dynein Activity By Cytoplasmentioning
confidence: 99%
See 1 more Smart Citation
“…This distribution is similar to that of glucose transporter-4 (GLUT-4), which in muscle and adipose cells traffics in an insulin-regulated manner between the cell surface and exocytic storage vesicles, but it is also partially contained in early (recycling) endosomes (50,51).…”
Section: Discussionmentioning
confidence: 70%
“…1). Additionally, more recent works have suggested that insulin recruits GLUT4 to the plasma membrane from the postendosomal vesicle-associated membrane protein (VAMP) 1 -2-positive compartment as well as from the cation-dependent mannose-6-phosphate receptor (CD-M6PR)-positive compartment that is dynamically shuttling between endosomes and the trans-Golgi network (TGN) (6,7). While such a diversity of the subcellular localization of GLUT4 would hamper our understanding of the insulin-regulated trafficking of GLUT4, it implies that the transit of GLUT4 to and from such distinct subcellular compartments would be regulated by different signals and trafficking machinery (e.g.…”
mentioning
confidence: 99%